Anti-Inflammatory Effect of Triterpene Saponins Isolated from Blue Cohosh (Caulophyllum thalictroides). (5th September 2012) - Lee, Yeonju; Jung, Jae-Chul; Ali, Zulfiqar; Khan, Ikhlas A.; Oh, Seikwan
Abstract : Blue cohosh has been used as a medicinal herb in eastern North America. It was commonly used as traditional medicines for the treatment of menopausal symptoms, rheumatic pain, and as anti-inflammatory remedy. Particularly, extract of blue cohosh roots has been used as anti-inflammatory antipyretic in traditional medicines. In the present study, we investigated the effects of blue cohosh components on the suppressive expression of iNOS or proinflammatory cytokines after the activation of microglia with lipopolysaccharide (LPS). The expression of iNOS, TNF- α, IL-1 β, and IL-6 was determined by western blotting or gene expression. Blue cohosh treatment suppressed the elevation of LPS-induced iNOS expression in a concentration-dependent manner in microglia cells. Blue cohosh constituents also suppressed the expression of TNF- α, IL-1 β, and IL-6. In addition, blue cohosh extract suppressed the expression of COX-2, iNOS, and proinflammatory cytokines in adrenal glands of mice. These results demonstrate that constituents of blue cohosh exert anti-inflammatory effects through the inhibition of expression of iNOS and proinflammatory cytokines. Therefore, blue cohosh may have therapeutic potential for the treatment of inflammation-related diseases.